Analisis Aplikasi E-Buddy Pada Pengelolaan Arsip Surat Masuk (Studi Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Sidoarjo) - Mulyoto, Syafira Tabithasari; Utami, Dian Arlupi (Universitas Negeri Surabaya, 2023)
E-Buddy makes incoming mail documents more organised, fast processing and can be carried out remotely. However, in its implementation, problems were found that hindered the archive management process such as the E-Buddy application system being down during working hours, errors in the mail distribution process, and archive management activities carried out by student interns. The purpose of this research is to analyse the E-Buddy Application in the Management of Incoming Letter Archives. This research uses Read and Ginn's (2010) theory related to the life cycle of electronic archives including creation and storage, use and distribution, maintenance, and disposition. The type of research uses descriptive qualitative. The results showed that the creation and storage process carried out had been running well but the input process was carried out by student interns, the process of using and distributing E-Buddy was running well because it facilitated the search for document retrieval and the distribution of letters was carried out digitally but it was found that the letter distribution process was hampered due to miss perceptions on the subject of the letter, the maintenance process had not been running ideally because an archive retention schedule had not been carried out and E-Buddy was down during working hours due to maintenance and a high number of accesses, and the archive disposition process had not been running because there were no rules regarding the method of document destruction in E-Buddy. The suggestions proposed are the need for accuracy in reading incoming letters to minimise distribution errors, the need for a document retention schedule, the creation of rules or guidelines related to the method of destruction or electronic documents, the management of incoming letters is carried out by DPMPTSP employees or by adding employees to the position, the E-Buddy maintenance process can be carried out outside working hours and increasing access capacity on the server to reduce downtime in the E-Buddy application.